HUBUNGAN DOKTER DAN PASIEN DI RUMAH SAKIT PENDIDIKAN - Nurismail, Eko Novanto; Corputty, Dian Yelisa; Dewanti, Intan Putri; Lada, Christina Olly; Buntoro, Ika Febianti Olly (Cendana Medical Journal, 2023)
The doctor-patient relationship, in this case communication, empathy and ways of serving patients, can be explored from an early age and continue to be developed and upheld by a doctor for successful therapy and in an effort to improve public health in the future within the teaching hospital environment. The purpose of this review article is to determine the importance of the doctor-patient relationship in a teaching hospital environment. This review uses 40 journals as sources in order to improve doctor-patient relationships in teaching hospitals. From this review it can be concluded that the main goal that young doctors are expected to achieve apart from medical science is soft skills in the form of how to create optimal therapeutic relationships with patients which can be practiced continuously during the professional education period at the Teaching Hospital.